The Economy of Family Farming Production - Forero-Álvarez, Jaime (2013)
Based on the authors’ own research, and on a review of literature on the subject, we propose a conceptualization of two types of family farming, peasants and capitalized non-peasants family farmers. The focus is placed on partial monetization of the production model. The existence of a monetary and a non-monetary dimension is the key to explaining the economic rationality of these two production models. As a way of explaining the economic efficiency of family farmers, the article concludes with a new conceptualization, which is of micro scale economies. This concept takes up the ideas of other authors who asserted that small-scale farming is more efficient than large-scale farming. It then moves on, and away from this idea by proposing that both large and small-scale farmers can be efficient; the former by virtue of scale economies, and the latter by obtaining scale micro-economies.